フジ コウロ 1974 1975 ニオケル ヒョウメン スイチュウ ノ クロロフィル リョウ - 大野, 正夫; オオノ, マサオ; OHNO, Masao (国立極地研究所, 1976)
P(論文) 1974年11月26日から1975年4月17日まで,第16次南極地域観測隊海洋生物・定常観測の一項目として「ふじ」の航路に沿って,表面海水のクロロフィル-α量を測定した.西太平洋では,クロロフィル-α量は0.05-0.19mg/m^3を示し,セレベス海,マラッカ海峡は西太平洋よりも高い値を示した.インド洋では,クロロフィル量は0.08-0.16mg/m^3を示したが,ケープタウン近海は1.08-5.21mg/m^3という非常に高い値であった.南極海域もかなり高い値を示しているが,観測点により変動がはげしかった.流氷域に接した開水面では,1.04-2.01mg/m^3という高い値を示した. Chlorophyll-α determinations of sea water were conducted on board the FUJI during the cruise to Antarctica. The chlorophyll-α content was 0.05-0.19mg/m^3 in the western Pacific. In the Cerebes Sea, the content became higher than that in the western Pacific. The content was 0.08-0.16mg/m^3 in the Indian Ocean. The highest chlorophyll-α value (1.71mg/m^3) of surface water was obtained at Station 44 (51°8'S, 106°52'E) in the Antarctic Ocean. Outside the pack-ice region of the Antarctic Ocean the value was relatively low, but in the pack-ice region the value was high ranging from 1.04 to 2.01mg/m^3. departmental bulletin paper